Preconception care utilization and pregnancy outcomes among postpartum women at Komfo Anokye Teaching Hospital, Ghana - Timothy Kwabena Adjei; Timothy Kwabena Adjei; Opei Kwafo Adarkwa; Opei Kwafo Adarkwa; Evans Ansu-Yeboah; Esmond Ofori; Esmond Ofori; Bernard Arhin; Augustine Tawiah; Augustine Tawiah; Charles Mawunyo Senaya; Charles Mawunyo Senaya; et al. (Frontiers in Reproductive Health)
IntroductionMaternal and perinatal morbidities are alarming in Sub-Saharan Africa. However, most of these can be prevented through appropriate care and interventions including preconception care (PCC). There is paucity of data on the effect of PCC on pregnancy outcomes in Ghana. This study sought to determine the association between PCC utilization and late pregnancy outcomes among postpartum women at Komfo Anokye Teaching Hospital (KATH). The study also assessed factors associated with its utilization.MethodA total of 336 postpartum women from an unmatched 1:2 case-control study, were interviewed. Women with late adverse pregnancy outcomes (APO) in the index pregnancy constituted the case group while those with no APO made up the control group. For every case who gave consent, two consecutive controls were recruited until the sample size was attained. Categorical variables were compared using Chi-square (χ2) or Fisher's exact test as appropriate, while continuous variables were compared using student t-tests. Multivariable logistic regression analysis was performed to estimate the odds ratios and the association between PCC utilization and pregnancy outcomes as well as factors associated with PCC utilization.ResultsA total of 112 cases and 224 controls were analyzed with comparable mean ages (Cases-30.2 ± 5.97 vrs Controls-30.5 ± 5.89 years, p = 0.45). PCC utilization rates were significantly lower among women who suffered late APO (14.3%) than those who did not (25.0%) p = 0.0241. PCC utilization was protective of late APO (OR-0.582) but not statistically significant (95% CI, 0.256–1.324; p = 0.197). Factors associated with PCC uptake included pregnancy intention (OR- 22.781; 95% CI, 7.883–65.837; p = 0.001), knowledge of PCC (OR- 56.4; 95% CI, 16.105–197.517; p = 0.001) and pre-existing medical condition (OR-3.976; 95% CI, 1.009–15.677, p = 0.049).ConclusionPCC utilization rates are low among postpartum women. Women who utilized PCC were twice less likely to suffer any late APO outcome compared to those who did not, though this was not statistically significant. Knowledge of PCC, pregnancy intention, and the presence of pre-existing medical conditions are factors associated with PCC utilization. These findings underscore the need for enhanced PCC education and targeted interventions to improve its utilization, particularly among women at high risk of APO.